Knowledge and attitudes towards organ donation among non-health science students - Blaževičiūtė, Gabrielė; Pilžienė, Katažyna; Paulikienė, Simona (Slauga. Mokslas ir praktika, 2023)
Abstract. Organ transplantation is the most effective and acceptable treatment for end-stage organ failure [1], but there are more people waiting for organs than donors. Each person has the freedom to decide whether or not to be an organ donor based on his or her values, beliefs and knowledge, and his or her decision can often be influenced by the knowledge and understanding of organ donation and transplantation. This article analyses the knowledge and attitudes towards organ donation among non-health science students. The research method used was a survey and a purposive sample was formed. The study involved 103 non-health science students from higher education institutions. The survey revealed that the majority of students are aware of the shortage of organ donors in Lithuania, and are able to identify the types of people who can become organ donors and the types of organs that can be transplanted. Students are the least aware of the methods of expressing the wish to become a potential organ donor and the individuals who can make the final decision. There are no significant, statistically significant differences in knowledge about organ donation by gender, field of study, or possession of a donor card. It appeared that the majority of the subjects do not have a donor card but do not object to organ donation after their death.